Hybrid identities: Māori Italians challenging racism and the Māori/Pākehā binary - Houkamau, Carla; Giorgio, Adalgsia (Social Identities, 2021)
New Zealand's indigenous Māori were colonized by the British (now referred to as Pākehā). Scant systematic investigation addresses bicultural/biracial identity for Māori who identify with ethnic groups other than Pākehā. Taking a narrative approach and applying thematic analysis, this paper explores interviews with forty-four Māori Italians, conducted in New Zealand in 2013. We show how Māori Italians negotiate the challenge of constructing positive ethnic identities in a milieu where ethnic hybridity has been defined primarily in relation to the Māori-Pākehā colonial encounter. Focusing on racism and stigma, we demonstrate that Māori Italians run a gauntlet of identity challenges shaped by socio-political contexts. Conversely, Māori Italians draw boundaries between themselves and the dominant Pākehā culture and draw from both Māori and Italian identities to buffer discrimination from Māori, Pākehā, and Italians. Our analysis reveals a multiplicity of interpretations of Māori-Italian identity not yet articulated in social psychology or New Zealand literature.
Keywords: ethnic identity; identity; māori identity; racism

Transformations in Māori Women's Identity: Some Things Change, Some Stay the Same - Houkamau, Carla Anne (Qualitative Research in Psychology, 2011)
While Māori (the indigenous people of New Zealand) retain a strong collective identity, cultural heterogeneity renders traditional conceptualisations of Māori identity increasingly problematic. To demonstrate the diverse ways Māori define and express their own identities, this article reports research that uses life-story interviews to explore personal perceptions of identity among 35 Māori women ages 18–75. Content analysis revealed traditional cultural factors (particularly whānau/family commitment) were important for identity among all participants, although the expression of these factors differed along with age and background. Older women raised in rural communities expressed family commitment through participating in social and economic activities within their own tribal networks. Younger, urbanised Māori expressed their identities by choosing careers which advanced Māori interests, supporting Māori political aspirations, and forming close relationships with other urban Māori. Life-story excerpts are used to illustrate distinct intergenerational differences in expressions of Māori identity as well as descriptions of “Māoriness,” seldom articulated in literature on the topic. The need to expand current paradigms of Māori identity to incorporate the diversity of group members is emphasised.
Keywords: colonisation; ethnic identity; kaumātua; mana wāhine; māori identity; urbanisation

Te Hoe Nuku Roa: A Measure of Māori Cultural Identity - Stevenson, Brendan (He Pukenga Korero: a journal of Māori studies, 2004)
Keywords: ethnic identity; identity; mātauranga māori; tāngata whenua

What Is the Degree of Matauranga Maori Expressed through Measures of Ethnicity? - Awatere, Shaun (AlterNative: An International Journal of Indigenous Peoples, 2010)
This research hypothesized that respondents who have a good understanding of Matauranga Maori (Maori knowledge) are those with a secure cultural identity and are more likely to be concerned with the environment. A quantitative survey was carried out using two separate samples drawn from the Maori population; one from the general Maori population (N=331) in the city of Auckland and the other from a sub-tribe (N=61) whose traditional land has been encompassed by Auckland City. The responses from the survey presented a consistent environmental concern attitude across both samples and challenge a priori assumptions. The meaningfulness of a Maori cultural identity (MCI) measure to represent Matauranga Maori perspectives of the environment is discussed. The conclusion from the findings is that cultural identity is much more complex than an ordinal number and that caution should be used when employing the MCI measure.
Keywords: ethnic identity; identity; mātauranga māori

Who are the Māori “in-between”? Indigenous diversity and inequity across descent, ethnicity and Iwi knowledge - Greaves, Lara M.; Lindsay Latimer, Cinnamon; Li, Eileen; Hamley, Logan; Renfrew, Larissa; Sporle, Andrew; Milne, Barry (Ethnic and Racial Studies, 2023)
Policies increasingly reinforce the self-determination of Indigenous peoples, but issues remain around group definitions. Colonization has led to (de)identification with Māori (New Zealand's Indigenous peoples) identity markers. We explore differences between Māori on combinations of descent, ethnicity and Iwi (extended kinship group) knowledge in the 2013 Census, and self-reported discrimination. There were six groups within the Māori descent population: two did not know their Iwi – some identified solely as Māori ethnicity (2.8 per cent) – or Māori plus another ethnicity(-ies; 6.8 per cent); two did not identify as Māori ethnicity: more named their Iwi (7.2 per cent), than not (6.9 per cent); the largest groups knew their Iwi and identified as Māori ethnicity, either solely (30.8 per cent), or alongside another ethnicity(-ies; 34.3 per cent). We found a pattern of differences across demographics and discrimination, highlighting the complexity of Māori identity and the need to account for differences within Indigenous groups.
Keywords: crown policy; discrimination; ethnic identity; identity; whakapapa

Perceived discrimination predicts increased support for political rights and life satisfaction mediated by ethnic identity: A longitudinal analysis - Stronge, Samantha; Sengupta, Nikhil K.; Barlow, Fiona Kate; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (Cultural Diversity and Ethnic Minority Psychology, 2016)
Objectives: The aim of the current research is to test predictions derived from the rejection-identification model and research on collective action using cross-sectional (Study 1) and longitudinal (Study 2) methods. Specifically, an integration of these 2 literatures suggests that recognition of discrimination can have simultaneous positive relationships with well-being and engagement in collective action via the formation of a strong ingroup identity. Method: We test these predictions in 2 studies using data from a large national probability sample of Māori (the indigenous peoples of New Zealand), collected as part of the New Zealand Attitudes and Values Study (Ns for Study 1 and 2 were 1,981 and 1,373, respectively). Results: Consistent with the extant research, Study 1 showed that perceived discrimination was directly linked with decreased life satisfaction, but indirectly linked with increased life satisfaction through higher levels of ethnic identification. Perceived discrimination was also directly linked with increased support for Māori rights and indirectly linked with increased support for Māori rights through higher levels of ethnic identification. Study 2 replicated these findings using longitudinal data and identified multiple bidirectional paths between perceived discrimination, ethnic identity, well-being, and support for collective action. Conclusion: These findings replicate and extend the rejection-identification model in a novel cultural context by demonstrating via cross-sectional (Study 1) and longitudinal (Study 2) analyses that the recognition of discrimination can both motivate support for political rights and increase well-being by strengthening ingroup identity. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; community; discrimination; ethnic identity; hauora; identity; protest

Indigenous identity and environmental values: Do spirituality and political consciousness predict environmental regard among Māori? - Cowie, Lucy J.; Greaves, Lara M.; Milfont, Taciano L.; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2016)
Indigenous peoples often have a unique and deep connection to the land. However, quantitative research exploring this issue is scarce. The current research investigates cultural variation in environmental regard in New Zealand, where more recent settler groups have questioned the strength of Indigenous environmental regard. Study 1 examined differences in environmental regard held by Indigenous and non-Indigenous ethnic groups in a nationally representative data set, the New Zealand Attitudes and Values Study (N = 9,269). Māori (the Indigenous group) expressed the highest levels of regard for the environment on average, although there was also considerable variance among Māori as a group. Study 2 adopted an emic perspective to investigate which dimensions of Māori identity are related to higher environmental value specifically among Māori (N = 193). Bayesian regression indicated that sociopolitical consciousness—the extent to which participants recognize the importance of and stand up for Māori political rights—was linked with higher environmental regard. Contrary to predictions, belief in Māori spiritual concepts was not linked with increased environmental regard. These findings suggest that Māori tend to value the natural environment more than non-Indigenous New Zealanders at least in part because high environmental regard is central to Māori political consciousness. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: environment; environmental attitudes; ethnic identity; identity; land protection; spirituality

Māori, a politicized identity: Indigenous identity, voter turnout, protest, and political party support in Aotearoa New Zealand - Greaves, Lara M.; Sengupta, Nikhil K.; Townrow, Carly S.; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2018)
Political struggles are important to the identities of many indigenous peoples. This article examines identity as a predictor of crucial political outcomes—voter turnout, support for protest, and political party support—for Māori, the indigenous peoples of Aotearoa (New Zealand). We analyzed data from a national probability sample of Māori (N = 663) that included a scale of subjective identification with various aspects of Māori identity: the Multidimensional Model of Māori Identity and Cultural Engagement. Use of the scale allowed us to examine the facets of ethnic identity that predict political mobilization for indigenous peoples. As expected, the identity domain relating to political struggle, Socio-Political Consciousness, was positively associated with support for left-wing parties and Māori rights protest but negatively associated with support for the right-wing party. However, Socio-Political Consciousness did not relate to voter turnout. These results demonstrate the importance of ethnic identity as a key predictor of political behaviors for indigenous peoples. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; ethnic identity; kāwanatanga; political participation; political parties; voter turnout; voting

Maori identity and "political arithmetick" : the dynamics of reporting ethnicity - Kukutai, Tahu (2022)
Thesis (M. Soc.Sc. Demography)–University of Waikato, 2001. Includes bibliographical references (leaves 193-203)
Keywords: crown policy; ethnic identity; ethnicity

White Mothers, Brown Children: Ethnic Identification of Maori-European Children in New Zealand - Kukutai, Tahu H (Journal of Marriage and Family, 2007)
Studies of multiethnic families often assume the ethnic identification of children with the minority group results from the minority parent. This study examines an alternate view that mainstream parents also play an important role in transmitting minority ethnicity. It explores this argument using data from New Zealand on the ethnic labels mothers assign to their Maori-European children. It finds that European mothers are just as disposed as Maori mothers to designate their child as Maori, either exclusively or in combination. Two explanations, grounded in ethnic awareness and gendered inheritance, are proposed. Although neither satisfactorily predicts maternal designation decisions, the readiness of European mothers to identify their child as Maori underscores their role in diffusing Maori ethnicity.
Keywords: ethnic identity; ethnicity; interethnic marriage

Oh, you don’t look Māori: Socially assigned ethnicity. - Cormack, Donna; Borell, Belinda; Gillon, Ashlea (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2019)
Keywords: blood quantum; ethnic identity; ethnicity; identity; kaupapa māori; racism; white privilege

The relationship between socially-assigned ethnicity, health and experience of racial discrimination for Māori: analysis of the 2006/07 New Zealand Health Survey - Harris, Ricci B.; Cormack, Donna M.; Stanley, James (BMC Public Health, 2013)
In New Zealand, there are significant and long-standing inequalities in a range of health outcomes, risk factors and healthcare measures between Māori (indigenous peoples) and Pākehā (European). This study expands our understanding of racism as a determinant of such inequalities to examine the concept of socially-assigned ethnicity (how an individual is classified by others ethnically/racially) and its relationship to health and racism for Māori. There is some evidence internationally that being socially-assigned as the dominant ethnic group (in this case European) offers health advantage.
Keywords: discrimination; ethnic identity; ethnicity; health; identity; inequity; racism; trauma